An "interaction-mediating" strategy towards enhanced solubility and redox properties of organics for aqueous flow batteries. (March 2020) - Huang, Zhifeng; Kay, Christopher W.M.; Kuttich, Björn; Rauber, Daniel; Kraus, Tobias; Li, Hongjiao; Kim, Sangwon; Chen, Ruiyong
Abstract: Aqueous redox flow batteries using electroactive organic materials are currently attracting significant attention. However, the influence of supporting electrolytes on the aqueous solubility, electrochemical reversibility and chemical stability of the organic components has rarely been investigated. Here, a new electrolyte design strategy towards enhanced solubility and chemical stability of active materials is proposed by using interaction-mediating species. 3 molality aqueous imidazolium chlorides, with high ionic conductivity and water-like flowability, enable a record aqueous solubility of 4.3 M for a commercially available nitroxyl radical and reversible 2e − reaction of unmodified methyl viologen at moderate concentrations. With 0.6 M electrolyte, flow cell shows remarkable chemical stability of the nitroxyl radical, excellent cycling stability over 250 cycles at 80 mA cm −2, and a peak power density of 121.6 mW cm −2 at 175 mA cm −2 . Furthermore, nitroxyl radical catholyte with a concentration of 3 M is tested in a flow cell. It maintains an impressive steady energy efficiency of 65% at 30 mA cm −2 . This work paves a new way for the development of high performance aqueous electrolytes based on organic materials. Graphical abstract: Image 1 Highlights: A record aqueous solubility of 4.3 M 4-OH-TEMPO was achieved in aqueous imidazolium chloride. Electrochemically reversible 2e − reaction of unmodified methyl viologen dichloride was demonstrated. The strong interactions between the imidazolium cations and organic solutes were revealed by means of EPR spectroscopy. Aqueous flow battery was demonstrated at high catholyte concentration of 3 M 4-OH-TEMPO.